Lo Spazio Condiviso : artisti e architetti, Cosmorama, Divina Proporzione. - Brayer, Marie-Ange; Chiodi, Stefano; Fara, Giovanni Maria; Lupano, Mario; Migayrou, Frédéric; Risaliti, Sergio; Rota, Italo; Vinca Masini, Lara (Siena : Palazzo delle Papesse Centro Arte Contemporanea, 2000)
Andreu, Paul ; Architecture Principe ; Ban, Shigeru ; Basilico, Gabriele ; Besset, Pierre du & Lyon, Dominique ; Branzi, Andrea ; Buren, Daniel ; Casebere, James ; Coindet, Delphine ; Coop Himmelb(l)au ; Denari, Neil ; Eisenman, Peter ; Emmerich, David-Georges ; Friedman, Yona ; Graham, Dan ; Graham, Rodney ; Gursky, Andreas ; Honert, Martin ; Koolhaas, Rem ; Libeskind, Daniel ; Makoto Sei Watanabe - Architects' Office ; Matta-Clark, Gordon ; Morphosis ; Natalini, Adolfo ; NOX - Lars Spuybroek ; ONYX ; Oosterhuis, Kas ; Perrault, Dominique ; Pettena, Gianni ; Porro, Ricardo ; Quarmby, Arthur ; Raggi, Franco ; Rottier, Guy ; Rudiger, Bernhard ; Ruppersberg, Allen ; Saee, Michele ; Schein, Ionel ; Schulze-Fielitz, Eckhard ; Solomouhka, Kristina ; Stinco, Antoine ; Superstudio ; UFO ; UN Studio
biog. per kunstenaar
Italiaans & Engels
Lo Spazio Condiviso, Palazzo delle Papesse Centro Arte Contemporanea, Siena, 30.06 - 30.09.2000
boek